Commoning genomic solidarity to improve global health equality - Joy Y. Zhang (Elsevier, 2023)
Summary: This article underlines two key asynchronies between prevailing governing logic and expanding practices in somatic human genome editing that are hindering an effective and orderly translation of the new technology into public good. The first is a "genomic sovereignty" framing adopted by a number of non-Western countries that may exacerbate data biases in global research and that directs policy attention away from the necessary structural changes required to achieve non-discriminatory and equitable genomic healthcare. The other is a global deficiency in attending to "science at large": the challenge of regulating new assemblages of societal interests that advocate controversial or experimental research, often outside of conventional institutions and aided by "policy shopping." Both issues point to the fact that genomic research does not represent a well-defined scientific commons but rather a domain that requires active "commoning," with the aim of fostering genomic solidarity that coordinates responsible research within and across national boundaries.